Numerical simulation of the plastics injection moulding process - De Kock, Willem Johan (Department of Mechanical Engineering, 2016)
The Hele-Shaw formulation is widely used for the simulation of the injection moulding process. The influence of the Hele-Shaw approximations is, however, unknown. A two-dimensional numerical model based on the Hele-Shaw formulation, and a model based on the Navier-Stokes equations without the Hele-Shaw approximations were developed. The solutions obtained with these two approaches were compared to investigate the influence of the Hele-Shaw approximations on the simulation of the injection moulding process. Weakly compressible, non-Newtonian flow of an amorphous polymer melt under non-isothermal conditions were simulated using constitutive equations generalized to non-Newtonian materials. The finite volume method, which is a very powerful method yet easy to use, was used to discretize the governing equations as compared to finite element methods used in most other reported models. The influence of the Hele-Shaw approximations on the solutions of specific flow cases was determined by comparing the solutions obtained with the model based on the Hele-Shaw formulation and the model based on the Navier-Stokes equations. Parametric studies were done to compare the solutions of the two numerical models for a wider range of flow cases. The following conclusions were made as a consequence of this study: Numerical models to simulate the injection moulding process can be simplified and the computer time required to solve these models can be reduced by using the Hele-Shaw formulation instead of solving the full Navier-Stokes equations. Numerical models based on the Hele-Shaw formulation are well suited to simulate the injection moulding process when the geometries and flow conditions fall within certain limits. These limits are determined by the combined effect of the geometry and the flow conditions represented by the Reynolds number. The simplicity of the finite volume method used in the generalized Hele-Shaw model makes it an attractive model to use for injection moulding simulations.